Legal protection of Pet Animals in domestic legislation - Vidić Trninić, Jelena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The subject of the author’s analysis is the issue of legal protection of pet animals. Through analysis of applicable provisions contained in the Act on Animal Welfare of Serbia, on one hand, and the fundamental principles and provisions set out in the European Convention for the Protection of Pet animals, on the other hand, this paper attempts to point out the degree of legal protection that pet animals are awarded under domestic legal regulations, as well as to answer the question of compatibility of the national legislation with the international standards set out in the mentioned European Convention regarding the above mentioned question. In addition, since the legal protection of pet animals is also regulated by relevant by-laws in our law, the analysis of certain aspects of protection provided to pet animals, specifically the Decision of the city of Novi Sad on keeping of domesticated animals, the paper attempts to draw attention to compliance of the solutions adopted in this legal act, with the fundamental principles of protection, provided to pets by laws or the Act on Animal Welfare of Serbia. Finally, in order to provide a more comprehensive insight in terms of achievement of the legal protection of pets in Serbian law, the paper analyzes the types of unlawful conduct of the owner or the holder of the animals, as well as their respective sanctioning prescribed in specific laws or bylaws.